Multiplicative Method for Assessing the Technical Condition of Switching Bay Devices in a Substation Using Maintenance Priorities - Janez Ribič; Gorazd Štumberger; Marko Vodenik; Uroš Kerin; Miha Bečan; Anja Šketa; Peter Kitak; Drago Bokal (Applied Sciences, 2025)
This paper presents a novel method for assessing the technical condition of devices in the high-voltage (HV) switching bay of a substation, focusing on circuit breakers, disconnectors, and instrument transformers. These devices are typically maintained using a condition-based maintenance approach. The proposed method integrates data from individual maintenance tasks into a comprehensive assessment of each device’s technical condition. Traditionally, the technical condition and health index assessments rely solely on additive criteria. This study introduces an advanced assessment method that incorporates both additive and multiplicative criteria to enhance the prioritization of maintenance tasks. A data model is developed to extract the maintenance task data from device maintenance databases, enabling an automated assessment process. The proposed approach facilitates the generation of a c-curve throughout a device’s operational life. A comparison using real transmission system operator maintenance data demonstrates that the proposed method, which assesses device conditions using both additive and multiplicative criteria, outperforms the conventional approach that relies solely on additive criteria.